The Impact of Work Communication and Supervision on Employee Productivity: Case Study from PT Karajae Makmur Lestari in Mamuju Regency, Indonesia. - Apriandi, A.; Martini, Andi Indra; Yeni, Hari (Golden Ratio of Human Resource Management, 2024)
This study aims to analyze the effect of work communication and supervision on employee productivity at PT. Karajae Makmur Lestari in Mamuju Regency. A quantitative research approach was employed, with the sample selected using a probability sampling technique, resulting in 34 respondents. Data collection methods included observation, interviews, direct distribution of questionnaires, and documentation. The quality of the research instruments was tested using validity and reliability tests. The analytical method applied was multiple linear regression analysis, followed by hypothesis testing using the partial test (t-test) and simultaneous test (F-test). The findings of this study indicate that (a) Work communication has a significant partial effect on employee productivity. (b) Supervision also has a significant partial impact on employee productivity. (c)Work communication and supervision, when considered simultaneously, have a substantial effect on employee productivity. However, their combined contribution is relatively low, accounting for only 33.6%, while the remaining 66.4% is influenced by other factors not examined in this study.